Identification and evaluation of outcome measurement instruments in pyoderma gangrenosum: a systematic review. (1st November 2020) - Lu, J.D.; Hobbs, M.M.; Huang, W.W.; Ortega‐Loayza, A.G.; Alavi, A.
Summary: Background: Pyoderma gangrenosum (PG) is a rare autoinflammatory skin condition that causes tissue destruction and subsequent painful ulcers. To date, there are no core domains or instruments for assessing PG severity in clinical trials, and current treatment paradigms rely on outcome measurements that have not been well characterized in the literature. Objectives: To perform two systematic reviews that (i) identify the outcome measurement instruments used in PG clinical trials and their corresponding domains and (ii) identify any associated validation studies and evaluate their measurement properties and methodological quality. Methods: We systematically searched the MEDLINE and Embase databases for PG outcome measurement instruments. We also systematically searched for PG instrument validation studies. We evaluated the measurement properties and methodological quality of validation studies using the 2018 COSMIN Risk of Bias checklist. Results: In total, seven clinical trials were included. These studies utilized a total of 20 different instruments, including 11 physician‐reported instruments, eight patient‐reported instruments and one composite instrument. Among these, 85% of the instruments lacked any validation data. Of the remaining three validated instruments (speed of healing, physician global assessment and resolution of inflammation), methodological quality was not available for half of the COSMIN categories. Conclusions: We identified 17 non‐validated outcome measurement instruments used in PG clinical trials. We conclude that PG validation studies are required for existing instruments, and new instruments need to be developed to inform the consensus process for the development of a core outcome set for PG. What is already known about this topic? Pyoderma gangrenosum (PG) is a rare autoinflammatory skin condition that has been characterized by multiple outcome measurement instruments in clinical trials. However, there is no consensus on the most validated and appropriate outcome measurement instruments. What does this study add? This study identifies and evaluates 20 unique outcome measurement instruments for PG in the literature. Of these 20, 17 lack any instrument validation data, highlighting the need for future studies. What are the clinical implications of this work? Despite the current use of several outcome measurement instruments, future studies should explore the validation surrounding these instruments, as no instruments can currently be recommended.